Psychosocial assessment in mental health - Trenoweth, Steve; Moone, Nicki (SAGE, 2017)
"Psychosocial and holistic approaches to assessment have become a central feature of modern mental health care. This practical and comprehensive book guides students through the theory and practice of psychosocial assessments to help them integrate the data as preparation for the effective planning of treatment and interventions. Key features: step-by-step guide on how to undertake each stage of the assessment process in practice; clinical staff and service users voices describing their experiences of the process; end of chapter exercises; reflections and considerations for practice."--Provided by publisher.